Vermögenswert Marke : Mit Brand Management messbar zum Unternehmenserfolg beitragen /: Mit Brand Management messbar zum Unternehmenserfolg beitragen. ([2019]) - Cloosterman, Marc; Hoekstra, Laurens
No abstract available